Answer:
![(MR^(2)\omega _(i))/((MR^(2)+mr^(2)))=\omega _(f)](https://img.qammunity.org/2020/formulas/physics/college/a9lx5rwv2v2ncpmc9ejvrnkii022o42260.png)
Step-by-step explanation:
Mass of small disc = m
radius of small disc = r
Mass of large disc = M
Radius of large disc = R
Initial angular speed = ωi
Let the final angular speed is ωf
As no external torque of applied on the system so the angular system remains constant.
I1 ωi = I2 ωf
MR^2 ωi = (MR^2 + mr^2) ωf
![MR^(2)\omega _(i)=(MR^(2)+mr^(2))\omega _(f)](https://img.qammunity.org/2020/formulas/physics/college/e8myql2j413uw4skgm6eyfja2s4o0um7jw.png)
![(MR^(2)\omega _(i))/((MR^(2)+mr^(2)))=\omega _(f)](https://img.qammunity.org/2020/formulas/physics/college/a9lx5rwv2v2ncpmc9ejvrnkii022o42260.png)